Diplomat Archaeologists’ Inquiries into Antiquities in Cyprus During the Second Half of the 19th Century - Gürsoy Şahin (Tarih Dergisi)
This study investigates the inquiries into antiquities from American and European diplomat archaeologists working in ancient historical areas of Cyprus during the second half of the 19th century. Between the 1850s and 1870s, the diplomat archaeologists who were active in Cyprus archaeology transferred the collections they’d gathered to European museums and enriched them, sometimes acting friendly and other times acting in a spirit of cutthroat competition. The Ottoman authorities enacted the Law of Antiquities in 1869 and 1874 under this circumstance in order to prevent antiquities in the country from being looted. In this scope, they transferred a portion of the works that had been obtained from the excavation on the island of Cyprus to the Müze-i Hümâyun [Imperial Museum] in Istanbul. After this, England took over the governance of Cyprus in 1878, with all the antiquities on the island falling into the possession of the English Government.